Correlation of maximal respiratory exchange ratio with anaerobic power and maximal oxygen uptake in anaerobic trained athletes - Selcen Korkmaz Eryılmaz; Metin Polat (IP Iermakov S.S., 2021)
Background and Study Aim. The respiratory exchange ratio (RER) is the ratio of the amount of carbon dioxide produced (VCO2) to the amount of oxygen uptake (VO2) is important. It indirectly informs about the predominant metabolic pathway to provide the energy needed during exercise. The relationship of maximal RER with aerobic and anaerobic capacity in athletes remains unclear. The purpose of this study was to investigate the relationship between maximal RER and anaerobic power and maximal oxygen uptake (VO2max) in anaerobic trained athletes. Material and Methods. Thirteen male alpine skiers (age 18.1 ± 3.1 years) competing in national and international competitions participated in the study. Athletes first performed an incremental treadmill run test to determine their VO2max (ml/kg/min), maximal RER (VCO2 / VO2) and maximal running speed (km/h). After 48 hours, the athletes performed the Wingate anaerobic test to determine peak power, mean power, minimum power, and fatigue index. Pearson correlation coefficients were used to examine the relations between variables. Results. Maximal RER was positively correlated with peak power (r = 0.587, p < 0.035), mean power (r = 0.656, p < 0.015) and minimum power (r = 0.674, p < 0.012). Maximal RER did not significantly correlate with fatigue index (p > 0.05). Maximal RER was negatively correlated with the VO2max (r = - 0.705, p < 0.007) and maximal running speed (r = - 0.687, p < 0.01). Conclusions. Maximal RER may be useful for evaluating anaerobic capacity in anaerobic-trained athletes. Measuring the maximal RER values of athletes during incremental exercise may provide information about physiological adaptations in response to physical training.